2015
DOI: 10.1017/s0950268815001569
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic burden of hand, foot and mouth disease in children in Shanghai, China

Abstract: In the near future, the inactivated enterovirus 71 (EV71) vaccine is expected to become available on the market in China. Since EV71 is a major cause of hand, foot and mouth disease (HFMD), the vaccine is expected to significantly reduce the number of cases, as well as the detrimental economic effect of the disease. However, for a national vaccination strategy to be developed, policy-makers need more information on the socioeconomic burden of EV71 HFMD infection. Based on the 2011 population data, we estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 10 publications
0
21
2
Order By: Relevance
“…The lost earnings of non‐working days of patients, caregivers and visitors were evaluated as $184.3, $184.3 and $95.3, respectively. These lost earnings were significantly higher than that of HFMD cases in Shanghai and lower than that of H7N9 patients in Jiangsu Province (Huo et al, ; Wang et al, ). Our study also revealed that 99.1% of patients had health insurance, but only 25.8% of costs of SFTSV infection were covered by reimbursement.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The lost earnings of non‐working days of patients, caregivers and visitors were evaluated as $184.3, $184.3 and $95.3, respectively. These lost earnings were significantly higher than that of HFMD cases in Shanghai and lower than that of H7N9 patients in Jiangsu Province (Huo et al, ; Wang et al, ). Our study also revealed that 99.1% of patients had health insurance, but only 25.8% of costs of SFTSV infection were covered by reimbursement.…”
Section: Discussionmentioning
confidence: 96%
“…A structured questionnaire, which was formulated according to the previous socioeconomic burden studies, was used to collect the information from patients with SFTS (Huo et al, ; Wang et al, ). The questionnaire contained four parts, concerning (1) demographic features such as age, gender, occupation and medical insurance; (2) course of illness and clinical experience, including day of onset, day of visiting a doctor and medical institution level; (3) direct costs towards SFTS cases, such as outpatient costs, inpatient costs, out‐of‐pocket costs for drugs, transportation, food, lodging expenses of cases, caregivers and visitors; and (4) indirect costs in relation to SFTS cases, including lost work days of patients, caregivers and visitors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of the cases were under 5 years old, and there was no different proportion between sexes [8]. A lot of public health resources had been spent for treatment, care and prevention program for HFMD in Thailand [9].…”
Section: Introductionmentioning
confidence: 99%